Efficiency of Islamic Banks in Indonesia: Service Coverage, Business Size, Financing and Profitability During a Pandemic - Nurcahyani, Anggita; Syarifudin, Efi; Nani (Journal of Finance and Islamic Banking, 2022)
Earlier studies on banking efficiency during the COVID-19 period have not considered the issue of service coverage due to work restrictions through PPKM and the trend of digitizing services. This study aims to map the efficiency of Islamic banks during a pandemic from a production perspective by utilizing labor, the number of offices, and equity as input variables. The output variable represents the bank's ability to generate total financing and operating income. The efficiency analysis in this study uses a Variable Return to Scale (VRS) approach by using secondary data in the form of financial reports and annual reports of 14 Islamic commercial banks registered with the Financial Services Authority (OJK) in the 2019-2021 period. The findings in the study are that, in general, most Islamic banks can maintain their productivity and efficiency during the pandemic. There was a decline in efficiency in 2020 but improved again in 2021. Islamic banks with the most service coverage and large business sizes, such as BSI (BNIS, BRIS, BSM) and BTPNS were able to keep their efficiency. Surprisingly, BMI maintained efficiency in 2019-2020 but experienced a significant decline in 2021. The practical implication of this research is that most Islamic banks can keep their performance during pandemics driven by various macroprudential policies and digital adaptation. Furthermore, it is recommended that the direction of efficiency projection is from the input side, such as employee reduction.